Blessed Among All Women: Women Saints, Prophets & Witnesses for Our Time - Garrity, Mariann (Cistercian studies quarterly, 2006)
The article reviews the book "Blessed Among All Women: Women Saints, Prophets and Witnesses for Our Time," by Robert Ellsberg.